Tantangan Pemerintah Daerah dalam Penyusunan Peraturan Daerah Desa Adat: Upaya dalam Penetapan Desa Adat di Indragiri Hulu, Riau - Hirzan, Adli; Abdul Mutalib, Mimi Hanida (Indonesian Journal of Religion and Society, 2020)
The objective of this article is to explain the challenges that occur in establishing customary villages. This research uses a qualitative approach with a case study design. This study uses thematic analysis, which aims to identify patterns and determine themes. Data collected using interviews and documentation. The results of the study found that there were four challenges in making regional regulations for the establishment of customary villages: first, the drafting period for the determination of customary villages was carried out in a short period. Second, not prioritizing socialization. Third, local wisdom is considered less critical for the sub-district government. Fourth, there is no follow-up from the local government to establish local regulations. The results of this study have implications for the miscommunication of local governments in understanding the village law no. 6/2014. As a result, local governments have not fully rearticulated the village law regarding the establishment of customary villages.